2018
DOI: 10.1021/acs.langmuir.8b02387
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Nucleation within Elastic Confined Spaces: Suitable Spacing and Elasticity Can Accelerate the Nucleation

Abstract: Elastic materials are candidates for process intensification of gas storage by forming gas hydrate. In this work, molecular dynamics simulations of hydrate nucleation in elastic silica double layers were performed to study the effect of elastic confined spaces on hydrate formation. It is found that in narrow confined spaces, hexagonal rings dominated the hydrogen bond network of water molecules established rapidly by a multisite nucleation mechanism. With molecules added, a bilayer water structure was formed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…On the one hand, hydrate nucleation usually occurs away from the solid surface 33–36 . This is because the solid surface is typically nonuniform and extremely hydrophilic on mesoscopic and microscopic scales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, hydrate nucleation usually occurs away from the solid surface 33–36 . This is because the solid surface is typically nonuniform and extremely hydrophilic on mesoscopic and microscopic scales.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical analysis revealed that methane hydrate formed more rapidly on hydrophilic solid surfaces than on hydrophobic surfaces and that the hydrate in solution exhibited homogeneous nucleation. It cannot be overlooked that some researchers demonstrated that hydrates tend to nucleate into a quasi‐homogeneous phase in solution and that surface wettability has little effect 33–36 . For example, using both analysis methods, Stephen et al 35 used neutron scattering experiments in conjunction with molecular dynamics simulations to demonstrate that the hydrate is homogeneous nucleation away from the solid surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas hydrate, a type of cage-like crystal structure constructed by water and gas molecules, is generally formed in a low-temperature and high-pressure environment. The gas molecules, such as methane, ethane, carbon dioxide, and so forth, are able to be enveloped by the cages of water molecules, forming structure I, II, and H hydrate. The formation of hydrate becomes a challenge in the development of deep-water fields, where the oil or gas is exposed to the environment of high pressure, low temperature, and water cuts. , Therefore, hydrate forms more easily in the deep water environment and increases the risk of plugging pipelines. Webb et al studied the effect of water fraction in a water-in-dodecane emulsion on the rheological behavior of a hydrate slurry via a high-pressure rheology apparatus. The results show that the viscosity of the hydrate slurry increases apparently with the increase of water fraction from 5 to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…For heterogeneous nucleation, many experimental and theoretical studies have suggested that solid particles could promote hydrate formation. Bai et al studied the kinetic pathway of CO 2 hydrate formation triggered by hydroxylated solid surfaces, revealing that the nucleation of CO 2 hydrate was a three-stage process and it tended to occur more easily on less hydrophilic surfaces. MD simulations by He et al suggested that the hydrophilic silica and hydrophobic graphite surfaces played a critical role in the promotion effect on CH 4 hydrate formation, though their promotion effects were substantially different .…”
Section: Introductionmentioning
confidence: 99%